IMPROVING ACHIEVEMENT MOTIVATION FOR MENTALLY DISABLED STUDENTS AT SCHOOL FOR EXCEPTIONAL CHILDREN SLB YPAC PANGKALPINANG - Rina Miftakhi, Diah; Amalin Ulfah, Widati (Berumpun: International Journal of Social, Politics and Humanities, 2019)
This research is globally aimed to improve the achivement motivation for the mentally disabled students. The specific objectives of this research are to improve: (1) students learning achievement for the mentally disabled students; (2) learning achievement for the mentally disabled students in SLB YPAC Pangkalpinang. This research desaign was desaigned with research and development desaign which produce development model of group dynamics learning for exceptional students which can increase achievement motivation for students. The final objective of this research development is producing development learning model based on group dynamics so that teaching and learning process can be more effective, eficient, and interesting. This research will produce development model of group dynamics learning for mentally disabled students so that can increase achievement motivation in exceptional school. This development learning model of group dynamics has three activities, there are learning through dream trees, learning through filling students’ identity, and learning through artistic creativity development by drawing and coloring. The result of these three activities of development group dynamics learning model can be used as the source to arrange the learning model especially for mentally disabled students. It can be done so that we can develop the mentally disabled students’ potencies and they can reach good achievements in study. Besides that, it can be the source for the teachers to have innovative learning model in teaching mentally disabled students at exceptional school (SLB) YPAC Pangkalpinang.